HAEMATOLOGICAL ASSESSMENT OF BITTER LEAF (VERNONIA AMYGDALINA) EFFICIENCY IN REDUCING INFECTIONS IN COCKERELS - Olobatoke, R. Y.; Oloniruha, J. A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
This study was conducted at the Teaching and Research farm of Kabba College of Agriculture, Ahmadu Bello University, Kabba, Nigeria in 2006. Its objective was to assess the antimicrobial effect of bitter leaf (Vernonia amygdalina) on performance and blood picture of cockerels. Twenty two-weeks old cockerels were selected and used for the study. They were divided into four groups of five, with each group representing a treatment and each bird in a group constituting a replicate. Air-dried and ground bitter leaf was mixed with commercial (starter and later grower) feed at 0, 5, 7.5 and 10 % inclusion levels. Each group of cockerels was fed with these rations respectively for eight weeks. Weight gain was recorded weekly while percent packed cell volume (PVC) of blood, and total blood leucocyte counts were measured at two-weekly intervals. Data generated were subjected to analysis of variance and differences between treatments mean tested at 5 % probability level. Results of this study revealed that bitter leaf increased significantly the feed conversion efficiency of cockerels when included in rations with the peak at 7.5% inclusion level. There was however no significant difference in the PVC and average leucocytes counts.